2002
DOI: 10.1183/09031936.02.00301002
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory oxygen improves quality of life of COPD patients: a randomised controlled study

Abstract: It is unknown whether acute response to ambulatory oxygen (O 2 ) predicts longer term improvement in health-related quality of life (HRQL) in chronic obstructive pulmonary disease (COPD) patients.The aims of this study were 1) to assess the short-term clinical impact, as determined by HRQL, of ambulatory O 2 in a 12-week, double-blind, randomised crossover study of O 2 (versus cylinder compressed air) of dyspnoeic but not chronically hypoxic COPD patients with exertional desaturation ¡88% (n=41), and 2) to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
1
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(116 citation statements)
references
References 32 publications
(36 reference statements)
4
104
1
7
Order By: Relevance
“…Patient preference was also discussed in two out of four studies. This is known to be important as the COPD literature has demonstrated that even patients shown to get benefited from oxygen do not always wish to receive it (Eaton et al, 2002;Currow et al, 2007). It is also a critical issue given the subjective nature of dyspnoea and the fact that patients often have difficulty in describing the sensation (ATS, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Patient preference was also discussed in two out of four studies. This is known to be important as the COPD literature has demonstrated that even patients shown to get benefited from oxygen do not always wish to receive it (Eaton et al, 2002;Currow et al, 2007). It is also a critical issue given the subjective nature of dyspnoea and the fact that patients often have difficulty in describing the sensation (ATS, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…17 By contrast, Eaton et al, who studied patients with COPD and exercise desaturation, found improved quality of life in their patients. 18 Fujimoto et al, who studied 75 patients with mild to severe COPD and mild hypoxemia, found that their desaturator patients walked farther in the 6-min walk test and had improved pulmonary pressure after administration of oxygen during exercise. 19 Jolly et al found that their patients, especially the desaturators, walked farther and suffered less dyspnea after oxygen administration.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our assessment was carried out at a single time point, using a 6MWT, so our results do not necessarily reflect the acceptance and effectiveness of this treatment in patients' daily lives. 31 Longer-term studies are needed to determine the impact on quality of life of the various oxygen-conserving devices.…”
Section: Discussionmentioning
confidence: 99%